TO STUDY THE IMPORTANCE OF ELECTRONIC WORD OF MOUTH AND TRUST ON ONLINE SELLERS IN SOCIAL MEDIA AMONG THE FEMALE COLLEGE STUDENTS IN KANYAKUMRI DISTRICT - Regina V; C.K. Sunitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Nowadays, social media platforms are widely used by people of all ages for various purposes. However, it is observed that the younger generation is mainly utilizing these platforms for both educational and entertainment purposes. As a result, my research focuses on young individuals who use social media for online shopping. My investigation focuses on how positive conversations, also known as EWOM influence consumers to trust retailers, and how this trust subsequently impacts consumers’ decisions to shop online. Most existing literature emphasizes the direct impact on consumer online shopping behavior. This study concentrates on young users of social media users. The data were collected from Agastheeswaram taluk in Kanyakumari district (Nagercoil and Chungankadai) with the help of survey instruments by adopting simple random sampling method of 150 sample respondents. Therefore, the findings of this study will assist online sellers in understanding the level of trust that users have in online transactions and their willingness to use social media platforms for such purposes.